Transisi Peralihan Kewenangan Bidang Pendidikan SMA/SMK di Provinsi Banten - Habibi, Fikri (Universitas Serang Raya, 2017)
The authority of SMA / SMK, originally managed by the Regency / City Government, has been transferred to the Provincial Government. It aims to increase and equal the quality of education. In Banten Province. there are several issues related to the transfer of authority, including asset administration, both human and physical assets, as well as the ability to provide good and equitable services, and budget readiness. There are two approaches to solve it. The first approach is cluster quality and achievement, the second is cluster of educational access. Both approaches have different program priorities. Inventory and validation of personnel, facilities and infrastructure of SMA/SMK must be submitted to the Province in order to obtain certainty related to the number and needs.